An atlas of genetic correlations between psychiatric disorders and human blood plasma proteome. Issue 1 (2020) - Cheng, Shiqiang; Guan, Fanglin; Ma, Mei; Zhang, Lu; Cheng, Bolun; Qi, Xin; Liang, Chujun; Li, Ping; Kafle, Om Prakash; Wen, Yan; Zhang, Feng
Abstract: Background: Psychiatric disorders are a group of complex psychological syndromes with high prevalence. Recent studies observed associations between altered plasma proteins and psychiatric disorders. This study aims to systematically explore the potential genetic relationships between five major psychiatric disorders and more than 3, 000 plasma proteins. Methods: The genome-wide association study (GWAS) datasets of attention deficiency/hyperactive disorder (ADHD), autism spectrum disorder (ASD), bipolar disorder (BD), schizophrenia (SCZ) and major depressive disorder (MDD) were driven from the Psychiatric GWAS Consortium. The GWAS datasets of 3, 283 human plasma proteins were derived from recently published study, including 3, 301 study subjects. Linkage disequilibrium score (LDSC) regression analysis were conducted to evaluate the genetic correlations between psychiatric disorders and each of the 3, 283 plasma proteins. Results: LDSC observed several genetic correlations between plasma proteins and psychiatric disorders, such as ADHD and lysosomal Pro-X carboxypeptidase ( p value = 0.015), ASD and extracellular superoxide dismutase (Cu-Zn; p value = 0.023), BD and alpha-N-acetylgalactosaminide alpha-2, 6-sialyltransferase 6 ( p value = 0.007), MDD and trefoil factor 1 ( p value = 0.011), and SCZ and insulin-like growth factor-binding protein 6 ( p value = 0.011). Additionally, we detected four common plasma proteins showing correlation evidence with both BD and SCZ, such as tumor necrosis factor receptor superfamily member 1B ( p value = 0.012 for BD, p value = 0.011 for SCZ). Conclusions: This study provided an atlas of genetic correlations between psychiatric disorders and plasma proteome, providing novel clues for pathogenetic and biomarkers, therapeutic studies of psychiatric disorders.